2020
DOI: 10.1021/acs.orglett.0c02757
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Fueled Transient Geometry Changes in Diphenic Acids

Abstract: Transient changes in molecular geometry are key to the function of many important biochemical systems. Here, we show that diphenic acids undergo out-of-equilibrium changes in dihedral angle when reacted with a carbodiimide chemical fuel. Treatment of appropriately functionalized diphenic acids with EDC (N-(3-(dimethylamino)propyl)-N′-ethylcarbodiimide hydrochloride) yields the corresponding diphenic anhydrides, reducing the torsional angle about the biaryl bond by ∼45°, regardless of substitution. In the absen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Interestingly, the structure of the final gel is different from that formed directly by the acid substrate, exhibiting superior mechanical properties. Our own group has recently shown that intramolecular anhydride formation can be used to generate geometry changes in diphenic acids, providing a simple building block for clamp‐like behavior [63] . We have also used EDC to generate transient anhydride crosslinks between polymer chains, [64] another system that is only possible because of the Type 2 mechanism.…”
Section: Type 2 Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the structure of the final gel is different from that formed directly by the acid substrate, exhibiting superior mechanical properties. Our own group has recently shown that intramolecular anhydride formation can be used to generate geometry changes in diphenic acids, providing a simple building block for clamp‐like behavior [63] . We have also used EDC to generate transient anhydride crosslinks between polymer chains, [64] another system that is only possible because of the Type 2 mechanism.…”
Section: Type 2 Systemsmentioning
confidence: 99%
“…[62] Interestingly,t he structure of the final gel is different from that formed directly by the acid substrate,exhibiting superior mechanical properties.Our own group has recently shown that intramolecular anhydride formation can be used to generate geometry changes in diphenic acids,p roviding as imple building block for clamplike behavior. [63] We have also used EDC to generate transient anhydride crosslinks between polymer chains, [64] another system that is only possible because of the Ty pe 2mechanism. Thecovalent crosslinks give more robust mechanical properties than typical transient supramolecular gels.S imilarly, Wang and Jiang have recently demonstrated the EDC-fueled polymerization of an octaacid monomer,g iving at ransient polymer network starting from asmall-molecule substrate.…”
Section: Hydration Of Carbodiimidesmentioning
confidence: 99%
“…In previous work, we demonstrated chemically controlled geometry changes using the water-soluble diphenic acids DP-Ac1 – DP-Ac3 , as shown in Figure a. On reaction with EDC, they form (intramolecular) anhydrides, giving rise to significant changes in the twist about the biaryl bond, as shown in Figure b.…”
Section: Introductionmentioning
confidence: 83%
“…Transient anhydrides were indeed generated, and multiple cycles were tolerated, but the systems were not kinetically well-behaved under our original conditions, preventing the analysis of structure−property effects. 29 Here, we report the expanded series of diphenic acid derivatives in Figure 1a. Suitable conditions for quantitative mechanistic analysis of EDC-induced anhydride formation have been identified.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We thus decided to examine the commercially available diphenic acid (1n), a symmetric molecule for which a -CO2H group is present at C-2`, with a much lower steric demand than i-Pr group (A-values of 1.2 vs 2.2), but with almost orthogonal phenyl rings. 18 It is worth mentioning that diphenic acid derivatives can be found in herbs and fruits and exhibit a range of therapeutic properties. 19 After using our optimized conditions in the ECDC of 1n with MeOH, we were pleased to isolate the spirolactone 2n in good yield, with the second -CO2H group intact.…”
Section: Scope and Limitations Of The Ecdc/isomerization Protocolmentioning
confidence: 99%